MBA Curriculum Review - Sorooshian, Shahryar; M., Waris; Senthil Kumar, T.; Hasahudin, Hassan; Ida Rizyani, Tahir; Nor Sofea, Iman (Faculty of Industrial Management, 2016)
A workshop was organised on 16th & 17th July 2016, to review the MBA Curriculum.